Управление нестационарными колебаниями бесконечно длинной цилиндрической оболочки - Янютин, Евгений Григорьевич; Воропай, Н. И. (НТУ "ХПИ", 2010)
Досліджено неосесиметричне деформування круглої пружної нескінченно довгої циліндричної оболонки під дією навантаження. Розглянуто керування прогином оболонки. Моделювання деформування оболонки виконується на основі уточненої теорії С. П. Тимошенко. При визначенні керуючої сили використано метод регуляризації А. М. Тихонова.

An asymmetric deformation of the cylindrical shell under impulse load is investigated. The shell is supposed to be round, elastic and infinitely long. The controlling of the shell deflection is considered. The simulation of the shell deforming is based on S. P. Timoshenko’s refined theory. The Tihonov's regularizing method is used at determination control forcе
Keywords: колебания оболочки; колебательные процессы; линейные колебания; управление колебаниями